2017
DOI: 10.3126/jmcjms.v4i1.16381
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic: A Comparative Study

Abstract: Background and Objectives: Type II diabetes mellitus (DM) is particularly common medical disorder and is leading cause of morbidity worldwide. The complication of DM is due to micro or macro vascular damage. The presence of an extensive microvascular circulation and abundant connective tissue in the lungs raises the possibility that lung tissue may be a target organ in diabetic patients and thus pulmonary function test can be affected by DM. This study was designed to compare pulmonary function test between Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Similar results were observed particularly with T2D group in other local studies done at Aga Khan University Hospital, Karachi, 11 Baqai Medical University Teaching Hospital, Fatima Hospital, and Combined Military Hospital, Malir Cantt, Karachi 12 and Mayo Hospital, Lahore. 13 The results are similar for the T1D group from the study of Martin-Frias et al 14 , however, none of the local studies reported these results. The more reduced values of FVC and FEV1 in T2D indicate the reduced alveolar epithelium thickening.…”
Section: Discussionmentioning
confidence: 52%
“…Similar results were observed particularly with T2D group in other local studies done at Aga Khan University Hospital, Karachi, 11 Baqai Medical University Teaching Hospital, Fatima Hospital, and Combined Military Hospital, Malir Cantt, Karachi 12 and Mayo Hospital, Lahore. 13 The results are similar for the T1D group from the study of Martin-Frias et al 14 , however, none of the local studies reported these results. The more reduced values of FVC and FEV1 in T2D indicate the reduced alveolar epithelium thickening.…”
Section: Discussionmentioning
confidence: 52%